(untitled) (Revista de Medicina Clinica, 2024)
Clinical Snapshot on "Role of Regional Oxygen Saturation in the Early Detection of Lower Extremity Ischemia" presented in Volume 8 Issue 1 of Revista de Medicina Clínica.